Authentic Leadership And Performance -Equations The 4 C’s Framework And Impact Of Positive Intelligence - Suri, Kulneet (Journal of Neonatal Surgery, 2025)
Stress is a central element inhibiting and overpowering the happiness quotient of people at work and in personal lives. A leader like any other human being experiences emotions due to their past and present, tunnel vision and blind spots, experiences. Authentic leadership offers intentionality, a genuine direction to teams-and empowers the people with strategies. Deep change and transformation get translated into success with happier teams as they are self-motivated, engaged and connected. Happier teams will have a high Positive Intelligence quotient, higher Emotional Intelligence and feel empowered to solve problems which is an insight into creating an environment where employees feel comfortable speaking up and voicing their opinions-even if those opinions differ from leadership—and this demonstrates effective leadership.